2012
DOI: 10.5402/2012/584287
|View full text |Cite
|
Sign up to set email alerts
|

POEMS Syndrome: A Report of 14 Cases and Review of the Literature

Abstract: POEMS syndrome is a rare paraneoplastic disorder associated with an underlying plasma cell dyscrasia presenting polyneuropathy, organomegaly, endocrinopathy, monoclonal protein, and skin changes. This study reviewed the clinical characteristics of 14 POEMS patients in Zhongshan hospital. The ratio of male to female was 9 : 5, and the average age was 47.1 years. The clinical manifestations were various, including motorial symptoms (weakness), sensory symptoms (numbness), lymphadenopathy, edema, abdominal disten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Based on case reports, highdose chemotherapy with autologous stem cell transplant seems effective in improving symptoms. 13 Our patient was treated with cyclophosphamide, bortezomib and dexamethasone followed by autologous stem cell transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Based on case reports, highdose chemotherapy with autologous stem cell transplant seems effective in improving symptoms. 13 Our patient was treated with cyclophosphamide, bortezomib and dexamethasone followed by autologous stem cell transplant.…”
Section: Discussionmentioning
confidence: 99%
“…[7] This was also seen in patients subjected only to corticosteroids for treatment. [8] There is no standard first-line therapy for newlydiagnosed POEMS syndrome but current treatment approaches provide a good prognosis based only on one randomized controlled study that has been completed. Treatment for newly diagnosed POEMS syndrome depends on the extension of disease.…”
Section: Discussionmentioning
confidence: 99%
“…1 Due to its rarity, the standard of care is not well established in the management of the disease. Recently, multiple studies have reported on the durable responses with autologous hematopoietic stem cell transplantation (auto-HCT), [2][3][4][5][6][7][8] which is accepted as standard treatment approach in eligible patients. 9 We had previously reported on the role of auto-HCT in a smaller cohort of POEMS patients.…”
Section: Long-term Durable Efficacy Of Autologous Stem Cell Transplanmentioning
confidence: 99%